ANALISIS KELAYAKAN FINANSIAL USAHA PENGGILINGAN PADI (Oryza Sativa L) DI KECAMATAN SUKADANA KABUPATEN KAYONG UTARA - Retno Muntarsih; Erlinda Yurisinthae; Komariyati Komariyati (Jurnal Sains Pertanian Equator, 2018)
This study aims to analyze the financial feasibility level of rice milling business and to analyze the sensitivity of rice milling business in Simpang Tiga Village, Sukadana sub-district, Kayong Utara Districk. This research was conducted in 3 sub-villages namely Siduk Hamlet as much as 3 units, 2 units of Semanai Hamlet and 2 units of Dusun Parit Bugis. The population in this research is 7 rice milling business and all become the research sample chosen purposive (intentionally). The analytical method used is with the investment criteria (NPV, Net B / C, IRR, and PP) and sensitivity analysis. The results showed that the rice mill business is feasible to run financially because the value of NPV is Rp. 218.709.133, IRR ranges 79%, Net B / C Ratio of 3,4, and PP ranges from 1 years 7 months. Result of sensitivity analysis showed that rice milling business did not affect to increase of operational cost 3,68% and decrease of benefit equal to 3,86%.